Identification and Characterization of a Novel Palmitoyl Acyltransferase as a Druggable Rheostat of Dynamic Palmitoylome in L. donovani - Ayana, R.; Yadav, Preeti; Kumari, Rajesh; Ramu, Dandugudumula; Garg, Swati; Pati, Soumya; Singh, Shailja (Frontiers in Cellular and Infection Microbiology, 2018)
Palmitoylation has been recently identified as an important post-translational rheostat for controlling protein function in eukaryotes. However, the molecular machinery underlying palmitoylation remains unclear in the neglected tropical parasite, Leishmania donovani. Herein, we have identified a catalog of 20 novel palmitoyl acyltransferases (PATs) and characterized the promastigote-specific PAT (LdPAT4) containing the canonical Asp-His-His-Cys (DHHC) domain. Immunofluorescence analysis using in-house generated LdPAT4-specific antibody demonstrated distinct expression of LdPAT4 in the flagellar pocket of promastigotes. Using metabolic labeling-coupled click chemistry method, the functionality of this recombinant enzyme could be authenticated in E. coli strain expressing LdPAT4-DHHC domain. This was evident by the cellular uptake of palmitic acid analogs, which could be successfully inhibited by 2-BMP, a PAT-specific inhibitor. Using CSS-Palm based in-silico proteomic analysis, we could predict up to 23 palmitoylated sites per protein in the promastigotes, and further identify distinctive palmitoylated protein clusters involved in microtubule assembly, flagella motility and vesicular trafficking. To highlight, proteins such as Flagellar Member proteins (FLAM1, FLAM5), Intraflagellar Transport proteins (IFT88), and flagellar motor assembly proteins including the Dynein family were found to be enriched. Furthermore, analysis of global palmitoylation in promastigotes using Acyl-biotin exchange purification identified a set of S-palmitoylated proteins overlapping with the in-silico proteomics data. The attenuation of palmitoylation using 2-BMP demonstrated several phenotypic alterations in the promastigotes including distorted morphology, reduced motility (flagellar loss or slow flagellar beating), and inefficient invasion of promastigotes to host macrophages. These analyses confirm the essential role of palmitoylation in promastigotes. In summary, the findings suggest that LdPAT4 acts as a functional acyltransferase that can regulate palmitoylation of proteins involved in parasite motility and invasion, thus, can serve as a potential target for designing chemotherapeutics in Visceral Leishmaniasis.